2017
DOI: 10.1021/acsami.7b03081
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field-Assisted Perovskite Film Preparation for Enhanced Performance of Solar Cells

Abstract: Perovskite solar cells (PSCs) are promising low-cost photovoltaic technologies with high power conversion efficiency (PCE). The crystalline quality of perovskite materials is crucial to the photovoltaic performance of the PSCs. Herein, a simple approach is introduced to prepare high-quality CHNHPbI perovskite films with larger crystalline grains and longer carriers lifetime by using magnetic field to control the nucleation and crystal growth. The fabricated planar CHNHPbI solar cells have an average PCE of 17.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…The photocurrent hysteresis behaviors are further investigated through the J-V characteristics of PSCs measured under different scan directions at a scan rate of 0.60 V/s and the results are shown in Figure 5b-d. The photocurrent hysteresis is quantitatively described by the hysteresis index (HI), which is defined as [72] where [28][29][30][31][32][33][34][35] The PPDs with the same device structure as that for PSCs is also investigated. Figure 6a presents the J-V characteristics of PPDs measured both in dark and under the monochromatic light at the wavelength of 500 nm with the light intensity of 0.28 mW cm -2 at room temperature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The photocurrent hysteresis behaviors are further investigated through the J-V characteristics of PSCs measured under different scan directions at a scan rate of 0.60 V/s and the results are shown in Figure 5b-d. The photocurrent hysteresis is quantitatively described by the hysteresis index (HI), which is defined as [72] where [28][29][30][31][32][33][34][35] The PPDs with the same device structure as that for PSCs is also investigated. Figure 6a presents the J-V characteristics of PPDs measured both in dark and under the monochromatic light at the wavelength of 500 nm with the light intensity of 0.28 mW cm -2 at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The perovskite active layer was prepared by a two-step method. [5,6,[34][35][36] (TPC) measurements were conducted on home-made setup as our previous reports. [39][40][41]…”
Section: Photovoltaic Devices Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…To resolve that, approaches by physical methods such as electromagnetic fields have been performed on the perovskite fabrication which have been reported to induce significant change in the structural and opto‐electronic properties of materials. [ 20–22 ] Recently, some groups have found that some reversible morphological and structural responses (normally described as electrostrictive and electroelastic properties [ 23 ] ) could be induced by certain external electric fields. Moreover, unlike classical perovskites and semiconductors, hybrid metal halide perovskites have shown excellent ion transport ability which has played an important part in their performance [ 24,25 ] and induced some unique behaviors in devices, e.g., significant hysteresis in J – V characteristics of PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The cell films with larger crystalline gain and longer carrier lifetimes had an average PCE of 17.84% and the highest PCE of 18.56% using an optimized magnetic field at 80mT. In contrast, the PSCs fabricated without a magnetic field give an average PCE of 15.52% and the highest PCE of 16.72% [22]. The effect of a magnetic field on the photocurrent generated by a bulk heterojunction solar cell made from poly-3-hexylthiophene (P3HT) and [6,6]-phenyl C61-butyric acid methyl ester (PCBM) was investigated.…”
mentioning
confidence: 96%